Design and performance simulation of a novel waste heat-driven liquid desiccant combined with transcritical CO2 refrigeration system for ocean-going vessels in typical shipping routes. (1st February 2023) - Wang, Zhe; Yu, Shui; Cao, Menglong; Ji, Yulong; Cai, Wenjian; Han, Fenghui
Highlights: A novel AC system of ships combined with tCO2 and LLD system was proposed. EJE subcooling was used to improve tCO2 refrigeration system on board. The optimal pressure of the system is 9.2 MPa, and the corresponding COP is 3.14. The use of dynamic load routes design is conducive to energy saving and comfort. Abstract: Worldwide concerns about greenhouse gas emissions and energy-efficient applications. A new type of air condition system is proposed, which consists of waste heat-driven solution dehumidification and ejector refrigeration enhanced transcritical CO2 (tCO2 ) system. The characteristic of the system when applied to ocean-going vessels was examined. The load variation of the system was calculated under different indoor design conditions and outdoor environments. The operation and supercooling enhancement of tCO2 refrigeration in hot waters were investigated, the optimal discharge pressure of the tCO2 system is 9.2 MPa, and the corresponding maximum COP is 3.14, which is 8 % lower and 22.18 % higher than the base system respectively; finally, select the classic route to calculate the dynamic load and power consumption of the route, the average power consumption of the dynamic load calculation system is 36 kW, which is 26.5 % less than the power consumption of the system under the design parameters. The proposed system is suitable for complex and changeable offshore operating conditions, realizes the university application of tCO2 systems in the shipping industry, and the calculation method of dynamic load is to reduce navigation energy consumption and meet the thermal comfort of local extreme environments.